Strategi Penegakan Hukum dalam Penyelesaian Praktik Mafia Tanah dengan Instrumen Hukum Perdata di Indonesia - Akbar Kurnia Rahman; Andiera Eko Ramadhanty; Elalia Sari Rusli; Maisye Angely Putri Purnomo; Umbu Landu Parangga; Wulan Dwita (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The aim of the research is to determine the implementation of the land mafia's framework in carrying out its mission. By knowing the steps taken or determined by the government in handling land mafia cases in accordance with civil law instruments in Indonesia. This research applies normative juridical methods to conduct legal studies which are a form of construction of established regulations and rules. The norms and rules that apply in society are defined as laws, and the laws and regulations that govern a nation contain statements about these guidelines. The results of this research show that efforts to implement law enforcement are mainly taken by the government to reduce the possibility of these problems occurring, namely by forming a Land Mafia Prevention and Eradication Task Force (STPPMT) as well as a Team for the Acceleration of Agrarian Conflict Resolution (TPPKA) as a group dedicated to eradicating the land mafia. . movement. Second, utilize internet resources and direct services to the BPN office to verify the validity of land certificates..